2011
DOI: 10.1093/nar/gkr783
|View full text |Cite
|
Sign up to set email alerts
|

RNA-binding protein HuR autoregulates its expression by promoting alternative polyadenylation site usage

Abstract: RNA-binding protein HuR modulates the stability and translational efficiency of messenger RNAs (mRNAs) encoding essential components of the cellular proliferation, growth and survival pathways. Consistent with these functions, HuR levels are often elevated in cancer cells and reduced in senescent and quiescent cells. However, the molecular mechanisms that control HuR expression are poorly understood. Here we show that HuR protein autoregulates its abundance through a negative feedback loop that involves intera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
125
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(131 citation statements)
references
References 80 publications
6
125
0
Order By: Relevance
“…5a-c). Consistently, genome-wide mapping of HuR-binding sites revealed its binding to many pre-mRNAs, and HuR can regulate both splicing and polyA site use [37][38][39][40][41][42] . The configuration of HuR-binding sites in CENPN exon 12, with two centrally located strong binding sites and additional (potentially weaker) binding sites along the exon (Supplementary Fig.…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…5a-c). Consistently, genome-wide mapping of HuR-binding sites revealed its binding to many pre-mRNAs, and HuR can regulate both splicing and polyA site use [37][38][39][40][41][42] . The configuration of HuR-binding sites in CENPN exon 12, with two centrally located strong binding sites and additional (potentially weaker) binding sites along the exon (Supplementary Fig.…”
Section: Discussionmentioning
confidence: 71%
“…Alternatively, HuR could locally regulate the 3 0 -splice site or the polyA site of exon 12, because one CLIP-seq study found HuR-binding sites in their vicinity ( Supplementary Fig. 6), and HuR can bind or affect the recruitment of splicing and polyadenylation factors to exons and polyA sites, respectively 39,41,42 . HuR dissociation from CENPN pre-mRNA in response to DOXO and CPT is consistent with ARTICLE previous evidence that HuR binding to RNA is affected by DNA damage [45][46][47] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Next, DEGs were compared with interacting mRNAs to reveal 61 Elavl targets misexpressed in HuR lo cells (Supplementary Figure 10c and Supplementary Tables 1 and 2). The Elavl1/HuR mRNA was among those identified validating our approach as it is regulated both by its protein and nElavls 12,35 and has been knocked down in HT-22 cells. To restrict our analyses to putative HuR targets, we examined whether the human homologs of these 61 mRNAs were identified to physically interact with HuR in PAR-CLiP 36,37 assays deposited in the DoRiNA 38 database; based on phenotypic relevance, we selected six such mRNAs.…”
Section: Hur Targets and Regulates A Group Of Rnas Involved In Oxidatmentioning
confidence: 84%
“…For example, it was shown that the mammalian PTB and Drosophila sex lethal proteins can modulate PAS recognition by competing with CstF64 for binding to the DSEs (Castelo-Branco et al 2004;Gawande et al 2006). Similarly, recent studies demonstrated that the RNA-binding protein HuR regulates the APA of its own transcripts by competing with CstF64 for binding to one of the alternative PASs, thereby suppressing its usage (Dai et al 2012;Mansfield and Keene 2012). Global analyses revealed that when Nova2, a brain-specific RNA-binding protein, binds to RNAs within the PAS regions, it tends to inhibit the usage of that PAS, possibly by a steric hindrance mechanism (Licatalosi et al 2008).…”
Section: Insights From Global Studies Of Apamentioning
confidence: 99%